Changes in amount and length of periods of stereotypic behavior in Jersey cows with and without access to pasture - Demba, Susanne; Rose, Sandra (Frontiers in Animal Science, 2023)
The aim of the present study was to investigate whether the access to pasture affects the stereotypic behavior of Jersey cows kept in loose housing systems. Therefore, a total of 21 randomly selected Jersey cows housed in two different investigation farms were observed once a week for four weeks in winter and summer, respectively, using the focal sampling method. On every examination day, each cow was observed for 15 min and the amount (AP) and length (LP) of periods, in which the cows showed stereotypic behavior within this observation time, were counted. Wilcoxon signed rank tests were carried out to estimate differences between pasture access and no pasture access regarding AP and LP. Welch two sample t-tests were performed to detect differences in AP and LP between the both investigation farms. The results of the study show significant differences between the option of pasture access and no pasture access regarding the values of AP and LP. The values of AP (p = 0.001) as well as the values of LP (p = 0.006) were lower when the cows had access to the pasture. No differences could be found between the investigation farms. It could be concluded that the access to pasture has a significant influence on the stereotypic behavior in Jersey cows. Further studies are needed to intensively analyze the causes of stereotypic behavior in Jersey cows.